The Initiation of the Microglial Response - Kato, Hiroyuki (Brain Pathol, 2006)
The initial response of microglia to ischemia and ischemia‐like conditions was analyzed in situ and in vitro. After sublethal ischemia in situ, microglia appear activated morphologically, but do not express macrophage‐like antigens. In contrast, neuronal damage induces full expression of immunomolecules in microglia. Additionally, blood‐borne cells readily infiltrate the region of the ischemic core and constitute another source of cells with macrophage‐like expression. Thus, it appears that the microglia are the earliest cells to respond to injury, but their response is graded and complicated by the presence of blood‐borne immune cells. In vitro ischemia‐like conditions caused an irreversible depolarization, ion channel shutdown, and blebbing, indicating that microglia are not equipped to withstand an ischemic insult. Application of ATP alone to microglia produced outward currents and calcium transients and these calcium transients increased when ATP was applied in combination with high potassium. It is known that both outward currents and calcium transients are induced during spreading depression, a feature of focal injury, and this suggests that spreading depression might be one of the initial activators of microglia.